Influential Variables in the Saudi Political System (Descriptive-analytical study) - Hewa Abdulkhaleq Ahmed; Amin Faraj Sharif (Zanco Journal of Human Sciences, 2020)
Since its first era, the Saudi state has been based on many internal variables, including the tribal system through which the Sauds were able to take control of other tribes voluntarily or forcibly, and the Wahhabi Salafism advocacy was the ideology through which they were able to unite tribes on the one hand, And legitimizing what they have done in order to unify the regions and then declare their desired state on the other hand, to come the economic variable dependent on oil provides them with the strength through which they have so far been able to maintain social and political cohesion internally, while the external variables contributed Their relations with the major powers are to maintain the values of survival and ensure continuity.